2014
DOI: 10.1007/s12403-014-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Release of Metals from Different Sections of Domestic Drinking Water Installations

Abstract: Different metals can leach from piping materials into the tap water, which can be of health concern. This study investigated in which amount abundant metals were released from different parts of domestic installations into the cold tap water. For the approximate spatial allocation of the metal releasing sources, a sequential water sampling protocol was used after three hours of stagnation time representing the first five litre of the water column. After stagnation ten sample volumes were collected in series. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Elevated Pb levels in full and partial profile sampling, generally in the 3 rd to 10 th L sample, have been shown previously. As examples: 30 homes in Montreal, Canada sampled after a short (15 min) stagnation period showed peaks in mostly 5 th L samples in single-family homes, and in 4 th and 7 th L samples in 11 semi-detached and two-family homes; 45 sites in Halifax, Canada sampled after 6 h stagnation averaged 5 and 12 μg/L in first and fourth L samples, respectively; 8 homes in three U.S. cities sampled after 6 h stagnation peaked in third to seventh L samples; 32 Chicago homes sampled on three occasions after 6 h stagnation showed peaks in 6 th to 10 th L samples; 8 homes in Cranston, RI sampled after 6 h stagnation showed the highest Pb levels in 4 th to 6 th L samples (both before and after partial LSL replacement); , based on measurements at 37 homes across 8 Midwest or eastern U.S. utilities, the 6 th L sample was determined to be the best for capturing Pb peaks, conversely, sequential sampling of several metals (e.g., Zn and Ni) found peaks in the first L sample in 2 of 11 homes sampled . This summary shows some variation in the timing and magnitude of Pb peaks and the modest sample size of earlier studies, and it generally supports the use of fourth to sixth L samples for homes with LSLs, as performed here.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated Pb levels in full and partial profile sampling, generally in the 3 rd to 10 th L sample, have been shown previously. As examples: 30 homes in Montreal, Canada sampled after a short (15 min) stagnation period showed peaks in mostly 5 th L samples in single-family homes, and in 4 th and 7 th L samples in 11 semi-detached and two-family homes; 45 sites in Halifax, Canada sampled after 6 h stagnation averaged 5 and 12 μg/L in first and fourth L samples, respectively; 8 homes in three U.S. cities sampled after 6 h stagnation peaked in third to seventh L samples; 32 Chicago homes sampled on three occasions after 6 h stagnation showed peaks in 6 th to 10 th L samples; 8 homes in Cranston, RI sampled after 6 h stagnation showed the highest Pb levels in 4 th to 6 th L samples (both before and after partial LSL replacement); , based on measurements at 37 homes across 8 Midwest or eastern U.S. utilities, the 6 th L sample was determined to be the best for capturing Pb peaks, conversely, sequential sampling of several metals (e.g., Zn and Ni) found peaks in the first L sample in 2 of 11 homes sampled . This summary shows some variation in the timing and magnitude of Pb peaks and the modest sample size of earlier studies, and it generally supports the use of fourth to sixth L samples for homes with LSLs, as performed here.…”
Section: Resultsmentioning
confidence: 99%
“…The high correlations between Pb and Zn, Cu, and Ni are also consistent with previous studies tracing brass fittings and fixtures as sources of Pb in drinking water. , For example, in their study of Pb in private drinking water systems in Virginia, Pieper et al found high correlations between Pb and Zn (ρ = 0.67), Cu (ρ = 0.61), and Ni (ρ = 0.56).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Cu contents were higher in water samples collected from new installations. The release of Cu from the material of connection is controlled by many factors, such as the water temperature or pH [100,102]. Zn can release from the galvanised pipes and other brass parts of water installation systems [103].…”
Section: Discussionmentioning
confidence: 99%